Progress in Artificial Intelligence
DOI: 10.1007/978-3-540-77002-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Stochastic Dynamics and the Spatial Prisoner’s Dilemma Game

Abstract: We argue that intermediate levels of asynchronism should be explored when one uses evolutionary games to model biological and sociological systems. Usually, only perfect synchronism and continuous asynchronism are used, assuming that it is enough to test the model under these two opposite update methods. We believe that biological and social systems lie somewhere between these two extremes and that we should inquire how the models used in these situations behave when the update method allows more than one elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…When this game is played using the proportional rule (see Section 2) it was found that sequential updating favors cooperation [13]. In our work with both games [2][3] [5] we confirmed the results of previous works but also found that asynchronous updating is detrimental for cooperation for very small noise values only, especially for regular networks. We also showed that the influence of the update dynamics depends mainly on the noise present in the strategy update process [4]: asynchronism becomes increasingly beneficial to cooperators as the noise level grows up to a certain value.…”
Section: Introductionsupporting
confidence: 89%
“…When this game is played using the proportional rule (see Section 2) it was found that sequential updating favors cooperation [13]. In our work with both games [2][3] [5] we confirmed the results of previous works but also found that asynchronous updating is detrimental for cooperation for very small noise values only, especially for regular networks. We also showed that the influence of the update dynamics depends mainly on the noise present in the strategy update process [4]: asynchronism becomes increasingly beneficial to cooperators as the noise level grows up to a certain value.…”
Section: Introductionsupporting
confidence: 89%
“…SFNs have a power law degree distribution P (k) ∼ k −γ that is also very common in real social networks 3 . SFNs are built in the following way: the network is initialized with m fully connected nodes.…”
Section: Interaction Topologymentioning
confidence: 91%
“…The influence of the update dynamics is addressed, for example, in [8] and [9]. We also studied the influence of the update dynamics and found that, in general an asynchronous dynamics supports more cooperators than a synchronous one [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To what extent does a random updating scheme change qualitative properties of a given system? For the sake of conciseness, we refer to [3,6] for a review of works related to asynchronism and for a discussion on updating schemes. The different types of convergence we exhibit, from very fast to very slow, seem to confirm that the updating scheme is an important factor to understand the evolution of a cellular automaton.…”
mentioning
confidence: 99%